Near-Infrared Laser-Triggered, Self-Immolative Smart Polymersomes for in vivo Cancer Therapy - Tang, Qing (Int J Nanomedicine, 2020)
PURPOSE: Traditional chemotherapy is accompanied by significant side effects, which, in many aspects, limits its treatment efficacy and clinical applications. Herein, we report an oxidative responsive polymersome nanosystem mediated by near infrared (NIR) light which exhibited the combination effect of photodynamic therapy (PDT) and chemotherapy. METHODS: In our study, poly (propylene sulfide)(20)-bl-poly (ethylene glycol)(12) (PPS(20)-b-PEG(12)) block copolymer was synthesized and employed to prepare the polymersome. The hydrophobic photosensitizer zinc phthalocyanine (ZnPc) was loaded in the shell and the hydrophilic doxorubicin hydrochloride (DOX·HCl) in the inner aqueous space of the polymersome. RESULTS: Under the irradiation of 660 nm NIR light, singlet oxygen (1)O(2) molecules were generated from ZnPc to oxidize the neighbouring sulfur atoms on the PPS block which eventually ruptured the intact structure of polymersomes, leading to the release of encapsulated DOX·HCl. The released DOX and the (1)O(2) could achieve a combination effect for cancer therapy if the laser activation and drug release occur at the tumoral sites. In vitro studies confirmed the generation of singlet oxygen and DOX release by NIR irradiation. In vivo studies showed that such a combined PDT-chemotherapy nanosystem could accumulate in A375 tumors efficiently, thus leading to significant inhibition on tumor growth as compared to PDT (PZ group) or chemotherapy alone (DOX group). CONCLUSION: In summary, this oxidation-sensitive nanosystem showed excellent anti-tumor effects by synergistic chemophotodynamic therapy, indicating that this novel drug delivery strategy could potentially provide a new means for cancer treatments in clinic.